Perceptions of emotional abuse in the coach-athlete relationship in youth sport: The influence of competitive level and outcome - Gervis, M.; Rhind, D.; Luzar, A. (International Journal of Sports Science & Coaching, 2016)
Emotional abuse has been highlighted as a key issue within the youth sport context. The present study investigated how perceptions of emotional abuse are influenced by situational factors. Two hundred and eight participants (107 athletes and 101 coaches) were shown a series of vignettes depicting emotionally abusive behaviour by a coach towards a 14-year-old athlete. Differences in perceptions were explored in relation to the level of competition (elite, county and club) and performance outcome (successful/unsuccessful) depicted in the vignette. Participants rated each vignette on a 5-point scale in terms of the extent to which the coach`s behaviour had an impact on the athlete`s performance and well-being as well as the perceived commonality and acceptability of the behaviour. Two-way ANOVAs revealed that competitive level and performance outcome, both as main effects and as an interaction, significantly influenced perceptions. These findings can inform policy and practice to change attitudes and behaviours which support and justify emotionally abusive behaviours in youth sport contexts. Emotionaler Missbrauch wurde als ein wichtiges Thema im Jugend-Sport-Kontext hervorgehoben. Die vorliegende Studie untersuchte, wie Wahrnehmungen von emotionalem Missbrauch durch situative Faktoren beeinflusst werden. Zweihundertacht Teilnehmern (107 Athleten und 101 Trainer) wurden eine Reihe von Vignetten gezeigt, die emotional missbräuchliches Verhalten eines Trainers gegenüber einem 14-jährigen Athleten darstellen. Unterschiede in der Wahrnehmung wurden in Bezug auf das Niveau der Konkurrenz (Elite, County und Club) und Performance-Ergebnis (erfolgreich/ erfolglos) in der Vignette dargestellt, untersucht. Die Teilnehmer bewerteten jede Vignette auf einer 5-Punkte-Skala in Bezug auf das Ausmaß, in dem das Verhalten des Trainers einen Einfluss auf die Leistung und das Wohlbefinden des Athleten sowie auf die wahrgenommene Gemeinsamkeit und Akzeptanz des Verhaltens hatte. Zwei-Wege-ANOVAs zeigten, dass das Wettbewerbsniveau und das Leistungsergebnis sowohl als Haupteffekte als auch als Interaktion signifikant die Wahrnehmung beeinflusst haben. Diese Erkenntnisse können Regeln und Verfahren vermitteln, um Einstellungen und Verhaltensweisen zu ändern, die emotional missbräuchliche Verhaltensweisen in jugendpolitischen Kontexten unterstützen und rechtfertigen. ABSTRACT FROM AUTHOR